Effects of cannabidiol on AMPKα2 /HIF-1α/BNIP3/NIX signaling pathway in skeletal muscle injury - Hou, Zhiquan; Wang, Zhifang; Zhang, Jun; Liu, Yunen; Luo, Zhonghua (Frontiers in Pharmacology, 2024)
Cannabidiol (CBD) is a non-psychoactive natural active ingredient from cannabis plant, which has many pharmacological effects, including neuroprotection, antiemetic, anti-inflammatory and anti-skeletal muscle injury. However, the mechanism of its effect on skeletal muscle injury still needs further research. In order to seek a scientifically effective way to combat skeletal muscle injury during exercise, we used healthy SD rats to establish an exercise-induced skeletal muscle injury model by treadmill training, and systematically investigated the effects and mechanisms of CBD, a natural compound in the traditional Chinese medicine Cannabis sativa L., on combating skeletal muscle injury during exercise. CBD effectively improved the fracture of skeletal muscle tissue and reduced the degree of inflammatory cell infiltration. Biochemical indexes such as CK, T, Cor, LDH, SOD, MDA and GSH-Px in serum of rats returned to normal. Combining transcriptome analysis and network pharmacology results, CBD may play a protective role in exercise-induced skeletal muscle injury through HIF-1signaling pathway. The experimental results implied that CBD could down-regulate the expression of IL-6, NF-κB, TNF-α, Keap1, AMPKα2, HIF-1α, BNIP3 and NIX, and raised the protein expression of IL-10, Nrf2 and HO-1. Molecular docking analysis showed that the core target and CBD were stable. These results indicate that the protective effect of CBD on exercise-induced skeletal muscle injury may be related to the inhibition of oxidative stress and inflammation, thus inhibiting skeletal muscle injury through AMPKα2/HIF-1α/BNIP3/NIX signal pathways.